Utilization of productive zakat funds in the ZMart Program to improve mustahik welfare - Abdul Rachman (Center for Islamic Economics and Development Studies [P3EI], 2022)
Purpose – This study aims to analyze the utilization of zakat funds carried out by BAZNAS Tangerang City through the ZMart program. Methodology – The method in this research is the descriptive qualitative method. The primary sources in this study were interviews and observations of the administrator of the ZMart BAZNAS program in Tangerang City, mustahik, who owns a ZMart store, and ZMart consumers. Secondary data sources come from several articles, data, and information related to the ZMart program.Findings – The results of this study illustrate that the utilization of zakat funds through the ZMart program is still unable to improve the welfare of mustahik towards muzakki because of the limited capital provided in managing their business, so they are only able to survive in managing a small shop. However, the ZMart application has been beneficial in managing small stalls even though the shop owners are still relatively low in using the latest technology.Practical implications – This research can be a source of data for BAZNAS Tangerang City and researchers, in general, to evaluate the ZMart program and its implementation to improve the welfare of mustahik towards muzakki.Originality – most studies analyze ZMart as a mustahik empowerment program focusing on the programs it does. This research focused on the results of the ZMart program, which can provide welfare in managing the business to increase the degree of mustahik to become muzakki.